2021
DOI: 10.1186/s12889-021-11813-6
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ and teachers’ views of the promotion of healthy eating in Australian primary schools

Abstract: Background Primary schools have long been identified as appropriate settings for improving the healthy eating behaviours of children and helping them develop food skills. This qualitative study explored the views of Australian primary school parents and teachers about schools’ strengths and weaknesses in promoting healthy eating and equipping children with food skills. Methods Nineteen parents and 17 teachers from Victoria participated in semi-stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 73 publications
1
10
0
2
Order By: Relevance
“…A previous qualitative study conducted by the authors in relation to parents and teachers' views of primary school FNE (Aydin et al , 2021a, b) and previous literature related to school FNE and food-related knowledge and skills informed the development of the instrument. A detailed description of the questionnaire has been reported elsewhere (Aydin et al , under review).…”
Section: Methodsmentioning
confidence: 99%
“…A previous qualitative study conducted by the authors in relation to parents and teachers' views of primary school FNE (Aydin et al , 2021a, b) and previous literature related to school FNE and food-related knowledge and skills informed the development of the instrument. A detailed description of the questionnaire has been reported elsewhere (Aydin et al , under review).…”
Section: Methodsmentioning
confidence: 99%
“…The obstacles to the effective participation of these professionals in the promotion of healthy eating in the school environment are the lack of local management guidelines and the lack of articulation with the head nutritionist of the Pnae. Studies have demonstrated that teachers help promote children's healthy eating (AYDIN et al, 2021;HASAN et al, 2021;RATHI;RIDDELL;WORSLEY, 2018;WEYBRIGHT et al, 2018). This is the first study to understand the opinion and involvement of educational professionals, through their own discourse about food and nutrition Education in schools.…”
Section: Resultsmentioning
confidence: 85%
“…The whole survey included thirty-one closed-ended questions with five associated sub-questions and seven open-ended questions. Previous qualitative studies we conducted in relation to parents’ and teachers’ views of primary school food and nutrition education and environments informed the development of the survey questionnaire (34,35) . The present paper reports the results from one closed-ended and one open-ended follow-up question and a variety of personal values and demographic questions (below).…”
Section: Methodsmentioning
confidence: 99%